The Contextualization Of Sayyid Idrus Bin Salim Al-Jufri's Thoughts On Religious Moderation In Institut Pendidikan Al-Khairaat Palu - Syarifa Abdul Haris; Muqowim Muqowim; Radjasa Radjasa (Universitas Muhammadiyah Malang, 2020)
Indonesia is a country with a diversity of ethnics, cultures, languages, and religions that make it a multicultural nation. It leads Indonesia vulnerable to conflicts because of the differences in the ways of thinking. Thus, religious moderation through Islamic Values of Wasatiyyah (NISWA) is expected to be a solution to this problem. Sayyid Idrus bin Salim Al-Jufri is one of the reformers in Central Sulawesi (Indonesian: Sulawesi Tengah) that engaged in education. By employing descriptive-analytic method, it can be inferred that Sayyid Idrus bin Salim Al-Jufri is a moderate figure. His thoughts manifested on his remarkable work, Institut Pendidikan Alkhairaat, keep growing up to now. The concept of Religious Moderation by Sayyid Idrus bin Salim Al-Jufri through Islamic values implemented in Education Institute Alkhairaat, heretofore, is following NISWA, are tawasuth, tawazun, tasamuh, musawah, islah, syura, i’tidal, aulawiyah, tahadlur, tathawur, ibtikar, and muwathanah.